FIRM SIZE, COST OF CAPITAL, AND FIRM PERFORMANCE: THE MEDIATING ROLE OF OPERATIONAL EFFICIENCY IN NON-FINANCIAL COMPANIES LISTED ON IDX - Khansaki Soullina Azzahra; Anis Chariri (Diponegoro Journal of Accounting, 2026)
This research aims to investigate the complex interplay between organizational scale, financing costs, and corporate outcomes through the lens of internal productivity. The study examines the influence of firm size and cost of capital on firm performance, specifically analyzing the mediating role of operational efficiency within non-financial companies listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024.Employing a quantitative approach, the investigation utilizes a purposive sampling method to select 61 companies, resulting in 183 observations over the three-year period. Data analysis is conducted using path analysis through the Fixed Effect Model (FEM), determined as the most appropriate estimation method after rigorous diagnostic testing, including the Chow and Hausman tests.The empirical findings indicate that firm size exerts a significant positive impact on firm performance, suggesting that larger enterprises benefit from superior resource configurations and economies of scale. However, the study reveals that cost of capital does not significantly affect operational efficiency. Furthermore, operational efficiency is found to have a negligible impact on firm performance within this specific temporal and industrial framework. Consequently, the results demonstrate that operational efficiency fails to act as a mediating variable between financial inputs and corporate performance. These findings highlight that for non-financial firms in Indonesia, market valuation as measured by Tobin’s Q is driven more directly by asset scale than by the optimization of internal operational ratios.